2006
DOI: 10.1128/iai.74.5.2937-2946.2006
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxigenicity of Mature 45-Kilodalton and Processed 35-Kilodalton Forms of Hemagglutinin Protease Purified from a Cholera Toxin Gene-Negative Vibrio cholerae Non-O1, Non-O139 Strain

Abstract: Cholera toxin gene-negativeVibrio cholerae non-O1, non-O139 strains are an intriguing group that can cause typical cholera-like disease but do not produce cholera toxin (CT) (23). The virulence factor in V. cholerae non-O1, non-O139 strains that do not produce cholera toxin and yet cause symptoms similar to cholera has not yet been identified (6). It was found that none of the previously described virulence-related genes like the RTX (repeats in toxin) toxin gene cluster, the hlyA gene coding for hemolysin, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…The expression of host-interacting adhesins/proteases by pathogenic bacteria is an important virulence mechanism that promotes host attachment, host protein degradation, tissue destruction, pathogen invasion, and dissemination of infection (56)(57)(58). To date, the only host component binding/degrading adhesins that have been identified in T. pallidum are Tp0750 and pallilysin (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of host-interacting adhesins/proteases by pathogenic bacteria is an important virulence mechanism that promotes host attachment, host protein degradation, tissue destruction, pathogen invasion, and dissemination of infection (56)(57)(58). To date, the only host component binding/degrading adhesins that have been identified in T. pallidum are Tp0750 and pallilysin (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…This raises the possibility that pro-EmpA has a role during infection by V. anguillarum that differs from that for mature EmpA metalloprotease. Perhaps EmpA, similar to Hap protease of V. cholerae, has bifunctional properties (10). How pro-EmpA may contribute to virulence of V. anguillarum is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In in vivo systems, the 45-kDa form can be processed to the 35-kDa form autolytically as well as by other general proteases found in the intestine. Additional studies have shown that HA/protease has bifunctional properties; the 45-kDa form is responsible for the enterotoxic response and the fully processed 35-kDa protease causes the HA activity responsible for the cytotoxic effects caused by this organism (10). We note that the processing of the pro-LasA to mature LasA protease in P. aeruginosa has been shown to involve the action of other secreted proteases, including elas-tase, lysine-specific protease (protease IV or PrpL), and alkaline proteinase (14).…”
Section: Discussionmentioning
confidence: 99%
“…This process has been linked to the virulence of many pathogenic bacteria, including Vibrio cholerae (27), Pseudomonas aeruginosa (48), and Legionella pneumophila (13,51), by observations that it promotes bacterial invasion and dissemination of infection via the degradation of structural tissue components and plasma proteins. Hostinteracting proteases have yet to be identified within T. pallidum at either an experimental or a bioinformatic level, although the highly invasive nature of this bacterium suggests their existence.…”
mentioning
confidence: 99%